Organochlorine pollutants in chub, Leuciscus cephalus, from the Svratka River, Czech Republic - Lána, R; Vávrová, M; Navrátil, S; Brabencová, E; Vecerek, V (Bulletin of environmental contamination and toxicology, 2010)
The aim was to evaluate the extent of pollution of the Svratka River with organochlorinated pollutants using the chub (Leuciscus cephalus) as a suitable bioindicator of the river contamination. The sum of 7 PCB congeners was found in range of 7.6-93.8 ng/g (with median of 31.7 ng/g) wet weight (ww), DDTs of 2.9-93.8 (29.9) ng/g ww, HCHs isomers of 0.1-5.3 (1.0) ng/g ww, HCB of 0.3-8.4 (2.2) ng/g ww and OCS of <0.1-0.5 (0.1) ng/g ww. Our results confirm predominance of metabolite DDE and higher-chlorinated PCB congeners and are comparable with similar studies and findings within the Czech Republic.
Keywords: Animals; svaly; Seasons; chemické látky znečišťující vodu; Tissue Distribution; Water Pollutants, Chemical; monitorování životního prostředí; Cyprinidae; Rivers; Hydrocarbons, Chlorinated; kůže; roční období; tělesná hmotnost; chlorované uhlovodíky; Czech Republic; Skin; řeky; Environmental Monitoring; tkáňová distribuce; Body Weight; Česká republika; Muscles; zvířata